Isolation of Mycobacterium branderi, an unusual species from an acute myelogenous leukemia patient - Majid Marjani (Thieme Medical and Scientific Publishers Pvt. Ltd., 2014)
We report a case of pulmonary infection caused by Mycobacterium branderi, a slow growing non-tuberculosis mycobacteria, in a patient with acute myelogenous leukemia. The pulmonary disease was treated successfully with the combination of Ciprofloxacin, Doxycycline and Clarithromycin. M. branderi may be considered as an opportunistic pathogen, especially among immunologically compromised patients.